Clinical and Radiological Outcome of Interlocking Intramedullary Nailing in Femoral Shaft Fractures: A Prospective Study (Community Based Medical Journal, 2026)
Femoral shaft fractures are common high-energy injuries, typically seen in young and active adults. Conservative treatment methods have largely been replaced by surgical fixation due to high complication rates and prolonged immobilization. Interlocking intramedullary nailing has become the gold standard for these fractures, providing axial, rotational, and angular stability while permitting early mobilization and rehabilitation. A prospective, observational study was conducted in the Department of Orthopaedics, Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, between January 2022 and December 2024, to evaluate the clinical, radiological and functional outcomes of femoral shaft fractures managed with interlocking intramedullary nailing. A total of 40 patients aged between 18 and 60 years with acute, closed diaphyseal fractures of the femur were included. Exclusion criteria were pathological fractures, Grade III open fractures, paediatric patients, and polytrauma cases with unstable vitals. All patients underwent interlocking intramedullary nailing under spinal/epidural anesthesia. Follow-up was done at 6 weeks, 3 months, and 6 months. Clinical and radiological union, complications, and functional outcomes were assessed. Functional evaluation was performed using Thoresen’s criteria. The mean age of the patients was 32 years, with males predominating (75%). Road traffic accidents accounted for 70% of injuries. AO classification revealed 32-A fractures as the most common (45%). Radiological union was achieved in 38 patients (95%), with a mean union time of 16.4 weeks. Complications included superficial infection (5%), limb length discrepancy >2 cm (5%), malunion (2.5%), and nonunion (5%). Functional outcome assessment showed excellent results in 70% of patients, good in 20%, fair in 5%, and poor in 5%. Interlocking intramedullary nailing is a safe, effective, and reliable procedure for femoral shaft fractures. It ensures high union rates, allows early mobilization, and yields excellent to good functional results in the majority of patients. Despite some complications, outcomes remain favorable compared to other treatment modalities, confirming its role as the gold standard for managing diaphyseal femoral fractures.   CBMJ 2026 January: vol. 15 no. 01 P:117-120